2021
DOI: 10.1007/s00122-021-03954-4
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of vigour-related traits in chickpea (Cicer arietinum L.): insights from genomic data

Abstract: Key message QTL controlling vigour and related traits were identified in a chickpea RIL population and validated in diverse sets of germplasm. Robust KASP markers were developed for marker-assisted selection. Abstract To understand the genetic constitution of vigour in chickpea (Cicer arietinum L.), genomic data from a bi-parental population and multiple diversity panels were used to identify QTL, sequence-level haplotypes and genetic markers associated with vigour-related traits in Australian environments. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 56 publications
(90 reference statements)
2
23
0
Order By: Relevance
“…In cool, short-season environments, increasing vigor is a key priority of breeding programs to improve competitive ability during crop establishment and yield. Genetic studies in many different crops have mapped vigor-related loci and assessed their impact under a range of growing conditions including irrigated, drought, salt, and disease pressure ( Collins et al, 1999 ; Graham et al, 2011 ; Platten et al, 2013 ; Sivasakthi et al, 2018 ; Taylor et al, 2019 ; Atieno et al, 2021 ; Nguyen et al, 2021 ). In chickpea, vigor has been reported to contribute either positively ( Subbarao et al, 1995 ; Turner et al, 2001 ) or negatively ( Zaman-Allah et al, 2011 ) to yield.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In cool, short-season environments, increasing vigor is a key priority of breeding programs to improve competitive ability during crop establishment and yield. Genetic studies in many different crops have mapped vigor-related loci and assessed their impact under a range of growing conditions including irrigated, drought, salt, and disease pressure ( Collins et al, 1999 ; Graham et al, 2011 ; Platten et al, 2013 ; Sivasakthi et al, 2018 ; Taylor et al, 2019 ; Atieno et al, 2021 ; Nguyen et al, 2021 ). In chickpea, vigor has been reported to contribute either positively ( Subbarao et al, 1995 ; Turner et al, 2001 ) or negatively ( Zaman-Allah et al, 2011 ) to yield.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, quantitative trait locus (QTL) mapping and association studies across multiple environments identified major genetic regions for vigor-related traits on chromosomes (Ca) 1, 3, and 4 in chickpea ( Nguyen et al, 2021 ). The vigor QTL on Ca4 ( Ca4_Vqtl ) overlapped with a “hotspot” region of QTL previously reported for drought tolerance ( Varshney et al, 2014 ; Jaganathan et al, 2015 ; Kale et al, 2015 ; Singh et al, 2016 ) and vigor ( Sivasakthi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations